2006
DOI: 10.1038/sj.npp.1301030
|View full text |Cite
|
Sign up to set email alerts
|

A Null Mutation of the Serotonin 6 Receptor Alters Acute Responses to Ethanol

Abstract: The anatomical distribution and pharmacology of serotonin 6 receptors (5-HT 6 Rs) implicate them as contributors to the serotonergic regulation of complex behavior. To complement the limited range of pharmacological tools available to examine 5-HT 6 R function, we have generated a mouse line bearing a constitutive null mutation of the 5-HT 6 R gene. No perturbations of baseline behavior were noted in a wide array of assays pertinent to multiple neurobehavioral processes. However, 5-HT 6 R mutant mice demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 73 publications
(78 reference statements)
1
30
0
Order By: Relevance
“…Thus, administration of either 5-HT 6 receptor antagonists or antisense oligonucleotides toward 5-HT 6 receptors decreases locomotion, induces chewing, yawning, and stretching, and improves performance in learning and memory tasks (Bourson et al, 1995;Sleight et al, 1996;Sleight et al, 1998;Yoshioka et al, 1998;Bentley et al, 1999;Rogers and Hagan, 2001;Woolley et al, 2001;Lindner et al, 2003;Riemer et al, 2003;Hatcher et al, 2005), while increasing anxiety Otano et al, 1999). 5-HT 6 receptor knock-out mice, however, perform normally in a wide variety of behavioral assays that assess cognition and anxiety (Bonasera et al, 2006). To our knowledge, the present study is the first to examine 5-HT 6 receptor function in relation to antidepressant-like activity and to indicate that 5-HT 6 receptor stimulation causes antidepressant-like behavioral and biochemical alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, administration of either 5-HT 6 receptor antagonists or antisense oligonucleotides toward 5-HT 6 receptors decreases locomotion, induces chewing, yawning, and stretching, and improves performance in learning and memory tasks (Bourson et al, 1995;Sleight et al, 1996;Sleight et al, 1998;Yoshioka et al, 1998;Bentley et al, 1999;Rogers and Hagan, 2001;Woolley et al, 2001;Lindner et al, 2003;Riemer et al, 2003;Hatcher et al, 2005), while increasing anxiety Otano et al, 1999). 5-HT 6 receptor knock-out mice, however, perform normally in a wide variety of behavioral assays that assess cognition and anxiety (Bonasera et al, 2006). To our knowledge, the present study is the first to examine 5-HT 6 receptor function in relation to antidepressant-like activity and to indicate that 5-HT 6 receptor stimulation causes antidepressant-like behavioral and biochemical alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, constitutive knockout mice for the 5-HT6 receptor display a reduced behavioral response to the acute effects of ethanol in adulthood, suggesting that impairments of the migration of GABAergic may contribute to the altered response to ethanol. 41 The 5-HT6 receptors are members of the G-proteincoupled receptor family and are positively coupled to adenylate cyclase. 42 We have shown that by modulating the cAMP signaling pathway we could inhibit or potentiate the effects of 5-HT6 receptor activation, suggesting that the effect of 5-HT6 activation on migration occurs via the cAMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the studies of Lieben et al (2005) and Woolley et al (2003), 5-HT 6 receptor antagonists did not improve memory consolidation in an object recognition test. Finally, there is a preliminary report that the (as yet poorly-documented) 5-HT 6 receptor agonist, Ro5035446, enhances performance in a novel object discrimination task (King et al 2006), while mice lacking 5-HT 6 receptors did not reveal improved performance in a Morris water maze test (Bonasera et al 2006). Thus, the precise significance of 5-HT 6 receptors in learning and memory processes remains in need of further elucidation.…”
Section: Introductionmentioning
confidence: 95%